Study of delayed cracking behaviors of hydrogen-charged SUS304L deep drawn cylindrical cups under elevated blank holding forces / Mohd Shahir Hadzir - Mohd Shahir, Hadzir (2022)
In this paper the effect of hydrogen charged SUS304L deep drawn cylindrical cups under elevated blank holding forces are investigated. A round SUS 304L blanks was deep drawn at 8, 9, 10 and 11 kN blank holding force, BHF using a die, after the specimens were hydrogen charged for 6, 12, and 24 hours in 1N of H2SO4 and As2O3 solution. It was found that the hydrogen charging of deep drawn cups has resulted in an accelerated appearance of the delayed cracks on the SUS 304L blanks. The 6 hours charged specimen was also deep drawn again using TiN coated die at 7, 10 and 12 kN of BHF, and it was found that delayed cracks still occur, but did not develop as fast as using uncoated die. Understanding the effect blank holding force with hydrogen towards the SUS304L will allow better understanding of the steel characteristic for future application.